(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Vortex tube is non-conventional system; in these natural substances e.g. air used is for refrigeration. Vortex flow phenomenon complex and compressible phenomenon. The solution of turbulent vortex flow is very difficult. In view of this an in house experimental facility is developed and which facilitate the testing on double nozzle vortex tube at various operating and design parameter such as L/D ratio, cold mass fraction ratio, operating pressure and cold end orifice diameter .In this study, past investigation of the design criteria of vortex tubes were overviewed and the detail summary is while designing it. Vortex tubes were classified and the type of them was described. All criteria on the design of vortex tubes were given in detail using experimental and theoretical results from the past until now. Finally optimum design of them is summarized.